Asymmetric Host Molecule Bearing Pyridine Core for Highly Efficient Blue Thermally Activated Delayed Fluorescence OLEDs. Issue 69 (27th October 2020) - Yoon, Jiwon; Kim, Seong Keun; Kim, Hyung Jong; Choi, Suna; Jung, Sang Won; Lee, Hyuna; Kim, Jun Yun; Yoon, Dae‐Wi; Han, Chang Wook; Chae, Weon‐Sik; Kwon, Jang Hyuk; Cho, Min Ju; et al.
Abstract: In this study, two host materials, pCzBzbCz and pCzPybCz, are synthesized to achieve a high efficiency and long lifetime of blue thermally activated delayed fluorescence organic light‐emitting diodes (TADF‐OLEDs). The molecular design strategy involves the introduction of a pyridine group into the core structure of pCzPybCz as an electron‐withdrawing unit, and an electron‐donating phenyl group into the structure of pCzBzbCz . These host materials demonstrate good thermal stability and high triplet energy (T1 =3.07 eV for pCzBzbCz and 3.06 eV for pCzPybCz ) for the fabrication of blue TADF‐OLEDs. In particular, pCzPybCz ‐based OLED devices demonstrate an external quantum efficiency (EQE) of 22.7 % and an operational lifetime of 24 h (LT90, time to attain 90 % of initial luminance) at an initial luminance of 1000 cd m −2 . This superior lifetime could be explained by the C−N bond dissociation energy (BDE) in the host molecular structure. Furthermore, a mixed‐host system using the electron‐deficient 2, 4‐bis(dibenzo[ b, d ]furan‐2‐yl)‐6‐phenyl‐1, 3, 5‐triazine (DDBFT) is proposed to inhibit the formation of the anion state of our host materials. In short, the device operational lifetime is further improved by applying DDBFT. The carbazole‐based asymmetric host molecule containing a pyridine core realizes a high‐efficiency blue TADF‐OLED showing a positive effect on the operating lifetime, and can provide useful strategies for designing new host materials. Abstract : Bipolar host : A high efficiency and long lifetime of blue TADF‐OLEDs is achieved by synthesizing pCzBzbCz and pCzPybCz host materials. The pCzPybCz ‐based devices exhibit a high EQE of 22.7 % and an operational lifetime of 24 h (LT90 ) at an initial luminance of 1000 cd m −2 .